2004
DOI: 10.1002/ab.20035
|View full text |Cite
|
Sign up to set email alerts
|

Attachment, emotional loneliness, and bullying behaviour: A study of adult and young offenders

Abstract: This research addresses the question of whether or not offenders who bully others and/or are victimised themselves can be distinguished by their attachment styles and the level of emotional loneliness that they report. Adult and young male offenders (n = 220) were required to complete a self-report behavioural checklist (DIPC: Direct and Indirect Prisoner behaviour Checklist: Ireland, 1999a) that addressed the level of bullying behaviour at their present institution. Offenders were also required to complete a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
2
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 22 publications
8
53
2
6
Order By: Relevance
“…The findings regarding adult male bully/victims are partially consistent with those of Ireland & Power (2004) reported in the English prisons that young and adult male bully/victims revealed higher insecure -avoidant, attachment scores than pure bullies and those not involved. However, the current findings are not consistent in terms of concrete insecure attachment styles with the first prediction, but generally supported the tendency for bully/victims to have distortions in secure attachment quality -in the present study dominant anxious/ambivalent; and in the previously mentioned study avoidant attachment style.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The findings regarding adult male bully/victims are partially consistent with those of Ireland & Power (2004) reported in the English prisons that young and adult male bully/victims revealed higher insecure -avoidant, attachment scores than pure bullies and those not involved. However, the current findings are not consistent in terms of concrete insecure attachment styles with the first prediction, but generally supported the tendency for bully/victims to have distortions in secure attachment quality -in the present study dominant anxious/ambivalent; and in the previously mentioned study avoidant attachment style.…”
Section: Resultssupporting
confidence: 87%
“…In the English prisons, dealing with young and adult violent and nonviolent offenders' attachment styles and their prison bullying behavior, respondents were grouped into four bully-categories: pure bullies, pure victims, bully/victims and not involved. Comparing differences between study groups in terms of secure, avoidant and anxious/ambivalent attachment it was revealed that bully/victims reported higher avoidant scores than the other bully-categories; with pure bullies and those not involved reporting lower avoidant scores (Ireland, & Power, 2004). …”
mentioning
confidence: 95%
“…The finding generally affirmed previous studies among children classified as avoidant type of attachment history and who most likely were aggressive and bully others in early and later childhood (Egeland & Sroufe, 1981;Renken et al, 1989;Troy & Sroufe, 1987). This finding is parallel with research results that indicated that children who bully were more likely to exhibit avoidant attachment in their adult relationships compared to those who began to bully as adults (Ireland & Power, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…An interesting find, which deserves more attention from investigators, is the fact that loneliness does not have a statistically significant relation with aggression. Some authors have verified that aggressors, in contrast to victims, do not present problems of loneliness, because they have a social support network that grants them esteem, respect, and confidence and that, at the same time, values them positively in terms of leadership and popularity (Estévez et al, 2005;Ireland & Power, 2004;Pellegrini & Bartini, 2000). However, our results indicate that loneliness intervenes directly in satisfaction with life, which is in accordance with the evidence obtained in this field of study (Heinrich & Gullone, 2006;Toner & Heaven, 2005).…”
Section: Discussionmentioning
confidence: 99%